PENGARUH MARKETING MIX DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KAIN TENUN MASRAIS SEBAGAI UPAYA MEMPERTAHANKAN EKSISTENSI PRODUK LOKAL DI TOKO TENUN DUA PUTRI - NABILA, SYAHRAINI; ERNAWATI, SRI; YUSUF, MUHAMMAD (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to investigate the influence of marketing mix and brand image on the purchasing decisions of Masrais woven fabric as an effort to sustain the existence of local products at Dua Putri textile store. The research method employed in this study is a survey method using a written questionnaire with 100 respondents as the sample. Data analysis includes validity testing, reliability testing, classical assumption testing, multiple regression analysis, correlation coefficient, determination coefficient, and hypothesis testing (t-test and F-test) using Statistical Product and Service Solution Ver.24 (SPSS) software. The results indicate that marketing mix significantly affects purchasing decisions, brand image significantly affects purchasing decisions, and both marketing mix and brand image significantly influence purchasing decisions.